Demographic Change Across The Globe Maintaining Social Security In Ageing Economies - Marga Peeters; Loek Groot (Economics and Econometrics Research Institute (EERI), 2011)
This paper investigates the fiscal pressure from demographic change in relation to the labour marketspace for fifty countries that cover 75% of the world population. The pressure-to-space indicator ranks Poland, Turkey and Greece high. Apart from Turkey and India, developing countries rank low due to low spending on the old (pensions, health care) and the young (education, family costs). Peculiarly, economies with higher pressure have more space. The hypothesis that ageing economies have started using their space in anticipation to higher demographic pressure is rejected. Raising the retirement age in developed economies by five years alleviates the pressure by almost 30% and creates 10% more labour market space.
Keywords: D6; E24; E62; H51; H52; H53; H55; J0; J11; J18; J21; J26; O57; 330; Demography; dependency rates; labour market; social security; pensions; government spending